Madrasah Principal Leadership in Digital Transformation at Madrasah Ibtidaiyah: A Case Study - Makherus Sholeh; Nur Kholis; Nuril Mufidah (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The rapid development of digital technology impacts the world of education. So, educational institutions need leader figures who can adapt to the development of digital technology. This article aims to explain the leadership of madrasah principals in digital transformation at MIN Blitar City. The method used is descriptive qualitative, collecting data using in-depth interviews, participant observation, and documentation, and data analysis using the Milles, Huberman, and Saldana’s model, namely data collection, data condensation, data presentation, and verification/conclusion. The main issues in digital transformation are: building awareness or understanding of technology, developing strategies and action plans for a suitable technology to be used in the digital transformation process, choosing the right human resources to succeed in technological change is followed by a change in technology-based work culture, fostering a culture of innovation and collaboration with the digital community, and carrying out supervision as a form of controlling the use of digital technology.